Mortui vivos docent [The dead teach the living] - Pidvalna, Uliana; Mateshuk-Vatseba, Lesya (Journal of Morphological Sciences, 2019)
Medical museums are a record of the history of the medical thought processes. The Anatomical museum of the Department of Normal Anatomy located in the Danylo Halytsky Lviv National Medical University was founded in 1894 by Professor Henryk Kadyi (1851–1912). The museum includes a number of unique objects and displays > 2,000 specimens. These medical artifacts include both normal anatomy and malformed artifacts. The museum is divided into three sections that are arranged according to the systems of the body and a method of preparing specimens. The vast array of preserved specimens represents comparative, developmental, gender, systemic, dynamic, plastic, and descriptive anatomy. Besides the Anatomical museum, the historical treasure is the Anatomical Theater, the oldest auditorium at the Danylo Halytsky Lviv National Medical University that preserved its authenticity. These educational places teach us not only about morphology, but also help us appreciate the beauty of the human body.
Keywords: history of morphological sciences; anatomical museum; Danylo Halytsky Lviv National Medical University; Henryk Kadyi